Repair of the Galeazzi Fracture. (August 2022) - Campbell, Hilary T.; Lowe, Dylan T.; Egol, Kenneth A.
Summary: This is a case of a 36-year-old female patient presenting with left forearm and wrist pain after a ground-level fall onto her outstretched left hand. Clinical and radiographic evaluation is consistent with a left distal radial shaft fracture with disruption of the distal radioulnar joint, known as a Galeazzi fracture. The purpose of this video is to review the appropriate management of Galeazzi fractures and demonstrate our treatment with this surgical approach.